2016
DOI: 10.3177/jnsv.62.213
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Relation to the Risk of Metabolic Syndrome in Middle-Aged and Elderly Patients with Type 2 Diabetes Mellitus

Abstract: Summary Vitamin D deficiency is highly prevalent all over the world and dietary intakes of vitamin D are very low in China. In this study we aimed to determine whether vitamin D deficiency is associated with increased risk of metabolic syndrome (MetS) among Chinese type 2 diabetes mellitus (T2DM) patients aged over 50 y. Vitamin D deficiency is now an increasingly recognized worldwide health concern (1) related to its nonclassical roles, such as diabetes, heart disease, autoimmune diseases and certain types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
2
16
0
2
Order By: Relevance
“…Recently, low vitamin D level (<30 ng/mL) was associated with increased risk of MetS (OR 1.90, 95% CI 1.26 to 2.85), and several of the cardiovascular risk factors comprised in MetS; high TG levels (OR 1.55, 95% CI 1.13 to 2.35), and low HDL-C levels (OR 1.60, 95% CI 1.19 to 2.40) [ 104 ]. This have also been found in other studies; MetS [ 105 ], WC [ 106 , 107 ], HDL-C [ 107 , 108 , 109 ], BP [ 107 ], and glucose [ 110 ].…”
Section: Nutritional Contribution Of Fishsupporting
confidence: 85%
“…Recently, low vitamin D level (<30 ng/mL) was associated with increased risk of MetS (OR 1.90, 95% CI 1.26 to 2.85), and several of the cardiovascular risk factors comprised in MetS; high TG levels (OR 1.55, 95% CI 1.13 to 2.35), and low HDL-C levels (OR 1.60, 95% CI 1.19 to 2.40) [ 104 ]. This have also been found in other studies; MetS [ 105 ], WC [ 106 , 107 ], HDL-C [ 107 , 108 , 109 ], BP [ 107 ], and glucose [ 110 ].…”
Section: Nutritional Contribution Of Fishsupporting
confidence: 85%
“…Evidence from observational studies have pointed that the role of vitamin D status and metabolic risk factors with non-diabetic adults (24,25) or patients with dia-betes (26), which was assistance with our study among Chinese adults with PreDM. However, the previous study did not find the association between a low serum vitamin D status and central obesity among prediabetic Korean adults (27).…”
Section: Discussionsupporting
confidence: 54%
“…And vitamin D might have a protective role in the underlying disorders of PreDM (22,23). To our knowledge, there have been several studies reported the positive relationship between vitamin D deficiency and MS and its components among adults with non-diabetic adults (24,25) or patients with diabetes (26). Although there was only one study has examined the association between serum vitamin D levels and metabolic risk factors among adults with PreDM in Korean (27), the result could not be directly applied to a Chinese population due to ethnic differences in vitamin D metabolism and its nutritional status (28).…”
mentioning
confidence: 95%
“… Authors’ assessment of the risk of bias in the diabetic subject studies: Data shown for each individual study (the plus sign shows a low risk of bias, the minus sign shows a high risk of bias, and the question mark indicates that the risk of bias is unknown) [ 22 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. …”
Section: Figurementioning
confidence: 99%